Explaining the multifaceted experiences of family caregivers of stroke survivors: a qualitative study in Iran - Kosar Pourhasan; Parvaneh Vasli (BMJ Open)
Objectives As the family caregivers of stroke survivors are typically subjected to care burden, spirituality has been advocated to protect them from its negative effects. The purpose of this study was to describe the caregiving experiences of family caregivers of stroke survivors.Design This qualitative study was conducted from December 2023 to June 2024 in Iran. Data were analysed using the conventional content analysis method.Setting The study was conducted in the neurology wards of two referral hospitals affiliated with Shahid Beheshti University of Medical Sciences in Tehran, Iran.Participants After meeting the inclusion criteria, a total of 17 family caregivers of stroke survivors were recruited using the purposive sampling technique with maximum variation. Data were then collected through 17 in-depth semistructured interviews, each lasting 30–60 min.Results Four themes emerged from the study participants’ statements: (1) ‘challenges and struggles’, (2) ‘religious coping strategies’, (3) ‘psychological coping strategies’ and (4) ‘social and relational dynamics’. The core concept of ‘balancing hope and hardship’ was then introduced.Conclusion The study findings highlight the need to develop comprehensive support programmes for family caregivers of stroke survivors to minimise their caregiving burden. Healthcare planners and providers are encouraged to use these findings to improve the health outcomes of these families and reduce the burden of caregiving.